Vulvar melanoma with multisystemic metastases: A rare case presentation (Indian Journal of Case Reports, 2022)
Malignant melanoma is the second most common vulvar malignancy which occurs in elderly females. In advanced stages of the disease, distant metastases can occur to any organ; hence, comprehensive radiological evaluation is necessary. We report a case of a 45-year-old female who presented with progressively increasing growth over the vulva for 6 months. On detailed clinical, pathological, and radiological workup, multiple metastases were found in the brain, liver, pancreas, peritoneum, lungs, and pleura. The final diagnosis of vulvar melanoma with multisystemic metastases was made after the histopathological examination.